2016
DOI: 10.1038/srep34768
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth promoting rhizobacteria Dietzia natronolimnaea modulates the expression of stress responsive genes providing protection of wheat from salinity stress

Abstract: Plant growth promoting rhizobacteria (PGPR) hold promising future for sustainable agriculture. Here, we demonstrate a carotenoid producing halotolerant PGPR Dietzia natronolimnaea STR1 protecting wheat plants from salt stress by modulating the transcriptional machinery responsible for salinity tolerance in plants. The expression studies confirmed the involvement of ABA-signalling cascade, as TaABARE and TaOPR1 were upregulated in PGPR inoculated plants leading to induction of TaMYB and TaWRKY expression follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
190
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(204 citation statements)
references
References 59 publications
12
190
0
2
Order By: Relevance
“…Also, inoculated tomato plants with certain PGPRs were shown to be able to maintain their growth under high-salinity and water-limited conditions by reducing the negative impact of stress-induced ethylene release on root growth through the activity of bacterial ACC-deaminase (Mayak et al, 2004). In a recent study, Bharti et al (2016) demonstrated the use of a carotenoid-producing halotolerant PGPR Dietzia natronolimnaea strain STR1 in conferring salinity tolerance in wheat.…”
Section: Salinitymentioning
confidence: 97%
See 1 more Smart Citation
“…Also, inoculated tomato plants with certain PGPRs were shown to be able to maintain their growth under high-salinity and water-limited conditions by reducing the negative impact of stress-induced ethylene release on root growth through the activity of bacterial ACC-deaminase (Mayak et al, 2004). In a recent study, Bharti et al (2016) demonstrated the use of a carotenoid-producing halotolerant PGPR Dietzia natronolimnaea strain STR1 in conferring salinity tolerance in wheat.…”
Section: Salinitymentioning
confidence: 97%
“…Inoculated plants had higher expression of proline and various antioxidants, enabling these plants to withstand salinity stress (Bharti et al, 2016). Moreover, ABA signaling, SOS pathways and iron transport were activated in these plants as a result of PGPR inoculation.…”
Section: Salinitymentioning
confidence: 98%
“…Recently, several studies demonstrated that the application of PGPR can significantly improve plant tolerance to salt stress (Egamberdieva and Lugtenberg ; Bharti et al . ; Habib et al . ; Sapre et al .…”
Section: Introductionmentioning
confidence: 99%
“…1.). Shoot development is sensitive to absence and inoculum dose (Bashan, 1986, Bharti et al, 2016, Lindberg et al, 1985. At low dose inoculum (da) the root percentage and root/shoot ratio have the highest values, with insertion in PCA Axis 1.…”
Section: Resultsmentioning
confidence: 99%